Estado del conocimiento de los métodos para instalar y rehabilitar redes de alcantarillado y acueducto con tecnologías Trenchless en Bogotá (2021)
Population growth implies an increase in the demand for public services and the obsolescence of the aqueduct and sewerage networks in urban areas, make necessary to carry out projects to rehabilitate and build infrastructure works of this nature; An ideal and versatile solution is to use Trenchless technologies due to the numerous advantages that they represent, such as the reduction of environmental and social impacts, the elimination of the negative implications of traffic and the effects on commercial areas, among others, that counteract the high initial costs required for installation.